PERCENTAGE OF DOGS SEROPOSITIVES FOR BRUCELLA CANIS THAT PRESENTED REPRODUCTIVE PROBLEMS THAT WERE ATTENDED AT VETERINARY TEACHING HOSPITAL OF THE STATE UNIVERSITY OF LONDRINA / Porcentagem de cães soropositivos para brucella canis apresentando ... - MACHADO, M. A.; SOLER, N. B.; FREITAS, J. C. (Ars Veterinaria, 2013)
A brucelose canina é uma doença infectocontagiosa, tendo como principal agente a Brucella canis. É caracterizada principalmente por abortamentos e esterilidade nas fêmeas, e orquite e epididimite nos machos. Possui caráter zoonótico e está mundialmente distribuída. Este estudo teve como objetivo investigar a ocorrência de anticorpos anti-Brucella canis em animais que apresentavam problemas reprodutivos e avaliar as características dos animais estudados, atendidos no Hospital Veterinário da Universidade Estadual de Londrina. Foram colhidas 22 amostras sanguíneas de cães machos e fêmeas, de idades, raças variadas, e sem raça definida. Estas amostras foram armazenadas e avaliadas pelo teste sorológico de imunodifusão em gel de agarose (IDGA). A soropositividade encontrada foi de 4,54%. Concluiu-se que apesar da baixa amostragem e baixa soropositividade, a infecção por Brucella canis ocorre em cães da cidade de Londrina e devem ser empregados estudos posteriores na cidade, bem como medidas de controle e profilaxia para evitar a disseminação do agente. SUMMARY Canine brucellosis is an infectious disease, the main agent is Brucella canis. It is mainly characterized by abortion and sterility in females and orchitis and epididymitis in males. It`s a zoonotic disease distributed worldwide. This study aimed to investigate the occurrence of antibodies to Brucella canis in animals that presented reproductive problems and evaluated the characteristics of these animals, that were attended in the Veterinary Teaching Hospital of the State University of Londrina. 22 blood samples were collected from male and female dogs of various breeds and ages, showing reproductive problems. These samples were stored and evaluated by serologic testing in agarose gel immunodiffusion (AGID). The seroprevalence found was 4.54%. It was concluded that despite the low sampling and low prevalence the Brucella canis infection occurs in animals of Londrina and further studies should be employed in the city, as well as prevention and in order to control to prevent the spread of the agent.